2020
DOI: 10.1109/access.2020.2992483
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of DCN-Based Super-Resolution

Abstract: Although DCN-based super-resolution (DCN-SR) techniques have shown impressive performance, the working mechanism has not been completely understood and DCN-SR methods still produce some artefacts. In this paper, we analyze the working mechanisms of DCN-SR methods. We derive mathematical formulations of the DCN-SR methods and provide some experimental analyses, which show that the effective receptive fields of the DCN-SR methods are considerably smaller than the theoretical receptive fields. Based on the mathem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In [20], it was shown that a convolution layer followed by a ReLU layer can be expressed by matrix operations. The patch was expressed as a vector (N x 1) with 2 NK = .…”
Section: A Dynamic Linear Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…In [20], it was shown that a convolution layer followed by a ReLU layer can be expressed by matrix operations. The patch was expressed as a vector (N x 1) with 2 NK = .…”
Section: A Dynamic Linear Transformationmentioning
confidence: 99%
“…The patch was expressed as a vector (N x 1) with 2 NK = . If there are 64 filters in the convolution layer, the convolution layer followed by the ReLU layer was expressed as follows [20]:…”
Section: A Dynamic Linear Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, deep convolutional neural networks (DCN) have been used for many SR problems and they have shown impressive performance improvement. Although the current DCN-based SR techniques have some limitations and reliability issues [44], they can provide noticeably improved performance compared to traditional SR methods under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%